La formación de recursos humanos para la oceanografía y las ciencias del mar - F. Raúl Gío Argáez (Ciencia Ergo Sum)
Because of their physical, chemical, geological and biological characteristics sea integrates a very complex and interesting ecosystem. For this reason research should also be interdisciplinary as well as multidisciplinary in order to link marine sciences and oceanography with society. In Mexico, the existing qualified staff does not satisfy the demand, both in quantity and in quality, to fulfill the positions necessary for the exploitation of renewable and non renewable natural resources. In this work it is proposed a revision of programs at schools, so that the education of scientific, technical and human resources specialized in marine sciences may satisfy present and future needs in the field of marine research and the inherent technological development.